Calculating the proportion of avoidable attendances at UK emergency departments: analysis of the Royal College of Emergency Medicine's Sentinel Site Survey data. Issue 2 (30th October 2017) - Morris, Toby; Mason, Suzanne M; Moulton, Chris; O'Keeffe, Colin
Abstract : Introduction: Avoidable attendances (AAs; defined as non-urgent, self-referred patients who could be managed more effectively and efficiently by other services) have been identified as a contributor to ED crowding. Internationally, AAs have been estimated to constitute 10%–90% of ED attendances, with the UK 2013 Urgent and Emergency Care Review suggesting a figure of 40%. Methods: This pilot study used data from the Royal College of Emergency Medicine's Sentinel Site Survey to estimate the proportion of AAs in 12 EDs across England on a standard day (20 March 2014). AAs were defined by an expert panel using questions from the survey. All patients attending the EDs were recorded with details of investigations and treatments received, and the proportion of patients meeting criteria for AA was calculated. Results: Visits for 3044 patients were included. Based on these criteria, a mean of 19.4% (95% CI 18.0% to 20.8%) of attendances could be deemed avoidable. The lowest proportion of AAs reported was 10.7%, while the highest was 44.3%. Younger age was a significant predictor of AA with mean age of 38.6 years for all patients attending compared with 24.6 years for patients attending avoidably (p≤0.001). Discussion: The proportion of AAs in this study was lower than many estimates in the literature, including that reported by the 2013 Urgent and Emergency Care Review. This suggests the ED is the most appropriate healthcare setting for many patients due to comprehensive investigations, treatments and capability for urgent referrals. The proportion of AAs is dependent on the defining criteria used, highlighting the need for a standardised, universal definition of an appropriate/avoidable ED attendance. This is essential to understanding how AAs contribute to the overall issue of crowding.